2023
DOI: 10.1021/acs.jafc.3c06238
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene as a Therapeutic Alternative for Central Nervous System Disorders: A Review of the Current Status and Perspectives

Xin Qu,
Lijuan Zhang,
Lin Wang

Abstract: Neurological disorders are diverse, have complex causes, and often result in disability; yet, effective treatments remain scarce. The resveratrol derivative pterostilbene possesses numerous physiological activities that hold promise as a novel therapy for the central nervous system (CNS) disorders. This review aimed to summarize the protective mechanisms of pterostilbene in in vitro and in vivo models of CNS disorders and the pharmacokinetics and safety to assess its possible effects on CNS disorders. Availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 233 publications
1
0
0
Order By: Relevance
“…The results show that resveratrol could delay articular cartilage degeneration by balancing HIF-1α and HIF-2α expressions and promoting chondrocyte autophagy, thereby regulating AMPK/mTOR signaling pathway . Similarly to our study, resveratrol was also reported to induce an inadequate assembly of ASC on the mitochondria and inhibit NF-κB responses, leading to the inactivation of NLRP3 inflammasome. However, the low bioavailability and rapid metabolization made the clinical application of these natural compounds ineffective. ,, PT, a dimethyl ether analog of resveratrol, shows better health effects due to its two dimethyl groups, which increase its bioavailability and result in a longer half-life in vivo . , In particular, several studies suggested that increasing the water solubility of PT significantly improves its oral absorption, thereby promoting the research on the production of highly water-soluble PT-modified compounds and increasing the research potential of PT. Our previous study demonstrated that PT could significantly attenuate renal fibrosis by downregulating NLRP3 inflammasome activation . Similar to the results in this study, PT affected the regulation of the NLRP3 inflammasome by reducing the expression of TGF-β-induced NLRP3.…”
Section: Discussionsupporting
confidence: 75%
“…The results show that resveratrol could delay articular cartilage degeneration by balancing HIF-1α and HIF-2α expressions and promoting chondrocyte autophagy, thereby regulating AMPK/mTOR signaling pathway . Similarly to our study, resveratrol was also reported to induce an inadequate assembly of ASC on the mitochondria and inhibit NF-κB responses, leading to the inactivation of NLRP3 inflammasome. However, the low bioavailability and rapid metabolization made the clinical application of these natural compounds ineffective. ,, PT, a dimethyl ether analog of resveratrol, shows better health effects due to its two dimethyl groups, which increase its bioavailability and result in a longer half-life in vivo . , In particular, several studies suggested that increasing the water solubility of PT significantly improves its oral absorption, thereby promoting the research on the production of highly water-soluble PT-modified compounds and increasing the research potential of PT. Our previous study demonstrated that PT could significantly attenuate renal fibrosis by downregulating NLRP3 inflammasome activation . Similar to the results in this study, PT affected the regulation of the NLRP3 inflammasome by reducing the expression of TGF-β-induced NLRP3.…”
Section: Discussionsupporting
confidence: 75%